2021
DOI: 10.1111/his.14438
|View full text |Cite
|
Sign up to set email alerts
|

Stromal composition predicts recurrence of early rectal cancer after local excision

Abstract: Stromal composition predicts recurrence of early rectal cancer after local excisionAims: After local excision of early rectal cancer, definitive lymph node status is not available. An alternative means for accurate assessment of recurrence risk is required to determine the most appropriate subsequent management. Currently used measures are suboptimal. We assess three measures of tumour stromal content to determine their predictive value after local excision in a well-characterised cohort of rectal cancer patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…Other factors, including fibrosis, stroma, PanIN, and fat content, did not differ significantly. However, a recent study reported that the ratio of desmoplastic to inflamed stroma is one of the clues to detect the recurrence of rectal cancer in the early stage after operation 27 . Related to this topic, a previous study reported that a low stromal area in cancer-involved regions is associated with poor prognosis, 28 although this study did not show any significant associations of stroma with outcomes and recurrences after surgery.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Other factors, including fibrosis, stroma, PanIN, and fat content, did not differ significantly. However, a recent study reported that the ratio of desmoplastic to inflamed stroma is one of the clues to detect the recurrence of rectal cancer in the early stage after operation 27 . Related to this topic, a previous study reported that a low stromal area in cancer-involved regions is associated with poor prognosis, 28 although this study did not show any significant associations of stroma with outcomes and recurrences after surgery.…”
Section: Discussioncontrasting
confidence: 54%
“…However, a recent study reported that the ratio of desmoplastic to inflamed stroma is one of the clues to detect the recurrence of rectal cancer in the early stage after operation. 27 Related to this topic, a previous study reported that a low stromal area in cancer-involved regions is associated with poor prognosis, 28 although this study did not show any significant associations of stroma with outcomes and recurrences after surgery. Hassid et al 29 indicated that patients with pancreatic cancer with high-grade PanIN showed a poor prognosis compared with patients with low-grade or non-PanIN.…”
Section: Discussionmentioning
confidence: 60%
“…38 Jones et al have also shown, thanks to machine learning algorithms, the importance of the composition of the tumor stroma and inflammation in the evaluation of the risk of recurrence from HE sections. 39 Other studies show the important impact on the prognosis of certain markers related to inflammation, 40,41 these markers can also be linked to the TNM score for more precision. 42 We noted an interesting difference in the segmentation of the 'immune cells' class, between IR and HE images.…”
Section: Deep Learning For Pfs Prediction From He and Ir Imagesmentioning
confidence: 99%
“…There have been several studies highlighting the relevance of tumour-stroma ratio/tumour cell proportion/tumour cell density/proportion of tumour (PoT) for prognosis prediction in CRC patients: High intra-tumour stroma content measured using different methods has been shown to predict poor prognosis in several different CRC patient cohorts [9] , [10] , [11] , [12] , [13] , [14] , [15] and other tumour types. Moreover, it has been suggested that tumour stroma is actively involved in CRC development and progression, and that disruption of the tumour-stroma interaction may inhibit tumour progression and metastasis formation [16] .…”
Section: Introductionmentioning
confidence: 99%